Efektivitas Mediasi Dalam Meminimalisir Angka Perceraian di Pengadilan Agama Kota Jambi - Aditya, Rezcky; Alissa, Evalina (Universitas Jambi, Fakultas Hukum, 2023)
The aims of this study are to find out and analyze the effectiveness of Mediation in minimizing divorce rates in the Jambi City Religious Court; and to find out and analyze the factors of the failure of Mediation in minimizing the divorce rate in the Jambi City Religious Court. The method used in this research is empirical juridical. The results of the research are based on what has been carried out as follows: that the effectiveness of mediation in minimizing the number of divorce in the Jambi Religious Court is still not effective, seeing from the results of the research conducted the number of divorce cases from 2020 to 2022 has increased, empowerment of mediation institutions in resolving civil cases, especially regarding the matter of divorce at the Jambi City Religious Court as evidenced by the small number of successful cases in Mediation. Based on the factors of the unsuccessful Mediation in the Jambi City Religious Court, the absence of the parties themselves, as well as the parties who are selfish and do not apply principles to resolve their problems peacefully, the absence of the parties will make it difficult for the Mediator to resolve the problem by reconciling the parties and the Mediator does not understand the problems faced by the parties so that the Mediation process is still not effective in reconciling the litigants, especially divorce cases.